2003
DOI: 10.1023/a:1024180101032
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The contraction of smooth muscle is regulated primarily by intracellular Ca2+ signal. It is well established that the elevation of the cytosolic Ca2+ level activates myosin light chain kinase, which phosphorylates 20 kDa regulatory myosin light chain and activates myosin ATPase. The simultaneous measurement of cytosolic Ca2+ concentration and force development revealed that the alteration of the Ca2+-sensitivity of the contractile apparatus as well as the Ca2+ signal plays a critical role in the regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…In addition, it is believed that Ca 2+ binds to calmodulin, and that Ca 2+ -calmodulin complex with catalytic subunit of MLCK activates enzyme to phosphorylate serine at position of 19 on MLC20 [Hartshorne, 1987]. However, Ca 2+ concentration does not always parallel the degree of MLC phosphorylation and contraction [Morgan and Morgan, 1984; Kanaide, 1999; Hirano et al, 2003]. When the extent of MLC phosphorylation or force of contraction induced by agonist stimulation is higher than that caused by a depolarization induced increase in the Ca 2+ concentration, this is called Ca 2+ -sensitization [Somlyo and Somlyo, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is believed that Ca 2+ binds to calmodulin, and that Ca 2+ -calmodulin complex with catalytic subunit of MLCK activates enzyme to phosphorylate serine at position of 19 on MLC20 [Hartshorne, 1987]. However, Ca 2+ concentration does not always parallel the degree of MLC phosphorylation and contraction [Morgan and Morgan, 1984; Kanaide, 1999; Hirano et al, 2003]. When the extent of MLC phosphorylation or force of contraction induced by agonist stimulation is higher than that caused by a depolarization induced increase in the Ca 2+ concentration, this is called Ca 2+ -sensitization [Somlyo and Somlyo, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…MLC2 phosphorylation is required for numerous cellular processes including cellular morphogenesis, cell movement, smooth muscle contraction, cytokinesis, and tumor cell invasion [22,23]. MLC2 is phosphorylated, primarily at serine 19, but also threonine 18, by a number of protein kinases, including Myosin Light Chain Kinase (MLCK), Rho-Associated Protein Kinase (ROCK), MRCKs, Integrin-linked kinase (ILK), and Zipper-Interacting Protein Kinase (ZIPK) [24]. In smooth muscle MLC2 is most often regulated by calcium-dependent pathways that leads to MLCK activation or by the RhoA-ROCK pathway [25].…”
Section: Resultsmentioning
confidence: 99%
“…The dephosphorylation of both sites on MLC2 is mediated by a highly conserved Myosin Phosphatase (MP) complex consisting of a targeting subunit Mypt1 and the catalytic subunit Protein Phosphatase 1 Beta (PP1β) [26]. MLC2 kinases and phosphatases are in turn precisely regulated by reversible phosphorylation in response to a variety of signaling pathways [24]. Importantly, not only do ROCK and ZIPK phosphorylate MLC2, but they also phosphorylate and inhibit the myosin phosphatase [26].…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has documented that the Rho-induced activation of ROCK promoted actin stress fiber formation by directly phosphorylating MLC in some cells. 34 Based on this fact, we hypothesized that MLC2 phosphorylation might participate in the actin-mediated oocyte meiosis in conjunction with RhoA. Our recent work demonstrated that both RhoA and ROCK participated in oocyte cytokinesis and spindle migration by mediating actin organization during oocyte meiosis.…”
Section: Discussionmentioning
confidence: 99%